Nietzsche and Wittgenstein: Cinematic Margins - Baranova, Jūratė (Religija ir kultūra, 2012)
The article consists of two logically independent parts. The first one deals with the influence of Wittgenstein and Nietzsche on the philosophy of cinema of Stanley Cavell and Gilles Deleuze, presupposing that the first one was more influenced by the former and the other one by the latter. The article also expresses some attempts to compare the two philosophies of cinema. The author discerns one common aspect: in opposition to the analytical and phenomenological trend, they both do not question the nature of cinematic experience and the intentionalism / nonintentionalism dilemma. On the other hand, they expose two different attitudes towards the meeting of thought and emotion in cinema practice. A detailed analysis of the integration of Nietszchean ideas in Deleuze’s philosophy of cinema reveals several possibilities for philosophy and cinema to meet. Firstly, the interpreter is able to use philosophical concepts for the experimental explanation of cinema; secondly, one can see cinema and philosophy as one problemic tisssue; thirdly, it is possible to consider (reasonably or not) some philosophical insights as an intention of the cinema director. The other part of the article is devoted to the image of Nietszche and Wittgesntein in the art of cinema, created by Liliana Cavani and Derek Jarman. The analysis shows that not all movies about philosophers have something to do with philosophy itself. The author discusses the four movies created by Cavani (The Night Porter (1974), Beyond Good and Evil (1977), The Berlin Affair (1983), Francesco (1989)), and concludes that one cannot discern any philosophical aspect in the movie Beyond Good and Evil on Nietzsche’s biography. On the other hand, it does not mean that biographical movies have nothing to do with philosophy. Derek Jarman’s movie Wittgesntein (1993) demonstrates the possibility of a creative integration of philosophical thinking into the tissue of the experimental cinema.